2021
DOI: 10.1111/spsr.12471
|View full text |Cite
|
Sign up to set email alerts
|

Wilful Non‐Compliance and the Threat of Disintegration in the EU’s Legal Order

Abstract: This article focuses on the problem of wilful non‐compliance with EU law and the threat it poses of (partial) disorderly disintegration within the EU’s legal order. Taking the example of migration and asylum policy following on from the 2015 migration crisis, I posit differentiated integration (DI), which occurs through processes that are formally mediated and collective, and non‐compliance, which is unmediated and unilateral, as alternative strategies for member states which are unwilling to accept further in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 45 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…Additional contextual evidence also suggests that states' propensity to violate EU law grew post-2004. Several cross-national crises plagued the EU during this period -such as the refugee and Eurozone crises (Genschel & Jachtenfuchs 2018;Scicluna 2021) -leading to highly publicized waves of member states flouting their EU legal obligations. As Commissioner Mario Monti acknowledged in a 2010 report, "the recent [Eurozone] crisis has shown that there remains a strong temptation, particularly when times are hard, to roll back the Single Market and seek refuge in forms of economic nationalism," making it more vital than ever that the Commission make "full use of its enforcement powers" (Monti 2010: 3).…”
Section: Quantitative Evidencementioning
confidence: 99%
“…Additional contextual evidence also suggests that states' propensity to violate EU law grew post-2004. Several cross-national crises plagued the EU during this period -such as the refugee and Eurozone crises (Genschel & Jachtenfuchs 2018;Scicluna 2021) -leading to highly publicized waves of member states flouting their EU legal obligations. As Commissioner Mario Monti acknowledged in a 2010 report, "the recent [Eurozone] crisis has shown that there remains a strong temptation, particularly when times are hard, to roll back the Single Market and seek refuge in forms of economic nationalism," making it more vital than ever that the Commission make "full use of its enforcement powers" (Monti 2010: 3).…”
Section: Quantitative Evidencementioning
confidence: 99%
“…First, unlike the ICRG data, these data do capture temporal variation within member states. Second, the underlying trends in Figure 6 are plausible since they coincide with several cross-national crises plaguing the EU during this period -such as the Eurozone crisis, refugee crisis, and COVID-19 pandemic -leading to generalized and highly-publicized waves of noncompliance (Genschel and Jachtenfuchs 2018;Scicluna 2021;Thym and Bornemann 2020). For instance, during the 2015-2016 refugee crisis, human rights NGOs "increasingly denounced EU member states' violations of the right of asylum and accused the EU of turning a blind eye to non-compliance with the CEAS [Common European Asylum system]" (Schmalter 2018: 1330).…”
Section: Figure 5 -Problematic Compliance Capacity Data: Data Used In...mentioning
confidence: 99%